(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
This paper outlines the recent Canadian experience of replacing the blanket prohibition of assisted suicide and voluntary euthanasia with a new regulatory regime for "medical assistance in dying". The aim is to illustrate how lawmakers in Canada have pursued the project that the Italian Constitutional Court has urged Italy’s parliament to undertake. Thus, the paper traces the arguments behind this law reform and highlighting ongoing disagreements over the manner in which it reconciles the protection of constitutional rights and the pursuit of particular policy objectives. Of course, the constitutional structures, political dynamics, medical cultures, and legal systems of these two countries differ in potentially salient ways. This paper is not a case for substituting Canada’s MAID regime for Italy’s current end-of-life laws whole cloth. Instead, the goal is to signal ways of thinking about, and responding to, some of the more pressing and difficult challenges to which efforts at law reform in this area may give rise.